Environmentally friendly room temperature synthesis of hierarchical porous α-Ni(OH)2 nanosheets for supercapacitor and catalysis applications. Issue 21 (8th October 2019) - Wang, Shaomin; Wang, Zhiwei; Wang, Yahuan; Chen, Jiafu; Chen, Zhimin; Chen, Yong; Fu, Jianwei
Abstract : Porous α-Ni(OH)2 nanosheets were facilely prepared via an aqueous co-precipitation reaction followed by a spontaneous ageing treatment at room temperature. Abstract : Porous α-Ni(OH)2 nanosheets are of special interest for many promising applications, while their large-scale green synthesis is still a considerable challenge. In this work, hierarchical porous α-Ni(OH)2 nanosheets were prepared using NiCl2 and NaBH4 as raw materials via a green and facile aqueous co-precipitation reaction followed by a spontaneous ageing treatment at room temperature. No surfactant, organic solvent or template was used in the process. The morphology and structure of resultant samples were fully characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), N2 sorption and X-ray photoelectron spectroscopy (XPS) and their electrochemical and catalytic properties were tested. The results showed that the prepared α-Ni(OH)2 sample has a high specific surface area of 393.4 m 2 g −1, large pore volume of 1.02 m 3 g −1 and hierarchical pores centered at micropores of about 1 nm and mesopores/macropores of about 3–100 nm. The intriguing structural feature endows α-Ni(OH)2 with superior electrochemical performance such as a large specific capacitance of 2378.7 F g −1 at a current density of 1 A g −1, a high rate performance with a specific capacitance retention of 70% from 1 to 10 A g −1 and good cycle stability with 71.7% retention after 3000 cycles at 10 A g −1 . Moreover, the hierarchical porous α-Ni(OH)2 nanosheets also exhibited excellent catalytic performance in the reduction of 4-nitrophenol with a reaction rate constant ( k ) of 0.33 min −1 . Additionally, the formation mechanism for porous α-Ni(OH)2 nanosheets was proposed based on SEM and TEM observations with different NiCl2 /NaBH4 ratios.